Sustaining the Use of Evidence-Based Tier 1 Literacy Practices That Benefit Students With Disabilities. (March 2023) - Wexler, Jade; Swanson, Elizabeth; Shelton, Alexandra; Kurz, Leigh Ann; Bray, Laura; Hogan, Erin
The adoption and sustainability of evidence-based Tier 1 literacy practices in secondary content-area classes is important to improve reading success for students with learning disabilities. We conducted an exploratory multiple-case study investigating teachers' adoption and sustained use of evidence-based Tier 1 literacy practices that benefit students with learning disabilities. The study was conducted within the context of an adolescent literacy model demonstration project funded by the U.S. Office of Special Education Programs (i.e., Promoting Adolescents' Comprehension of Text [PACT] Plus). Interviews were conducted with two administrators and seven teachers who sustained implementation of the PACT practices beyond 1 year of researcher support. Analyses revealed practice and school-level factors that influenced teachers' sustained use of the practices. We used findings from this study to propose a model of sustainability of Tier 1 evidence-based literacy practices used to improve outcomes for students with learning disabilities. Limitations and implications for future research are provided.